2017
DOI: 10.1186/s13047-017-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of rocker sole footwear for prevention of first plantar ulcer: comparison of group‐optimised and individually‐selected footwear designs

Abstract: BackgroundAppropriate footwear for individuals with diabetes but no ulceration history could reduce the risk of first ulceration. However, individuals who deem themselves at low risk are unlikely to seek out bespoke footwear which is personalised. Therefore, our primary aim was to investigate whether group-optimised footwear designs, which could be prefabricated and delivered in a retail setting, could achieve appropriate pressure reduction, or whether footwear selection must be on a patient-by-patient basis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…We excluded 28 of these articles based on irrelevant study population (n = 12), irrelevant study design (n = 4), irrelevant outcome/ intervention (n = 12) leaving 46 20‐65 included in the final review. As the initial search was undertaken in July 2016, updated searches were performed in December 2017 yielding 6918 articles, from which an additional three studies 66‐68 were included and November 2019 yielding 7821 articles from which a further five studies 69‐73 were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 28 of these articles based on irrelevant study population (n = 12), irrelevant study design (n = 4), irrelevant outcome/ intervention (n = 12) leaving 46 20‐65 included in the final review. As the initial search was undertaken in July 2016, updated searches were performed in December 2017 yielding 6918 articles, from which an additional three studies 66‐68 were included and November 2019 yielding 7821 articles from which a further five studies 69‐73 were included.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐four studies met the inclusion criteria. Study designs included: n = 13 RCT’s, 23,25,31,38,42,49,55,56,61,62,70,73,77 n = 37 cohort studies, 20‐22,24,26‐30,32‐37,39‐41,43,45,47‐49,51‐54,57‐60,64,66‐68,71,72 n = 2 case‐control studies, 44,63 n = 1 nonintervention case series study 46 and n = 1 nonrandomized cross‐sectional over trial 65 . Four authors reported results of the same study in different papers 21,22,39,40,45,47,49,50 and therefore results from these studies were described, but only one set of each results was used within any meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…4), clinicians need to decide whether the hallux is a greater priority for pressure relief than metatarsal heads. Alternative insole designs or pressure-reducing footwear [40] may be more appropriate in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…As a func# on of the placement of the rocker point rela# ve to the joint of interest, there are diff erent types: nega# ve heel, double or forefoot rocker. Modifying the angle rocker infl uences the value of the pressure under metatarso-phalangeal joints [38]. Standard types could be defi ned according to the joint of interest (ankle joint rocker, Lisfranc rocker, heel rocker, etc.).…”
Section: Shoe Sole's Prescrip• On Variablesmentioning
confidence: 99%